Trimetallic TriStar Nanostructures: Tuning Electronic and Surface Structures for Enhanced Electrocatalytic Hydrogen Evolution. Issue 10 (12th January 2016) - Du, Nana; Wang, Chengming; Wang, Xijun; Lin, Yue; Jiang, Jun; Xiong, Yujie
Abstract : PtFeCo alloy nanostructures in a TriStar shape with tunable Fe and Co content are developed for the electrocatalytic hydrogen evolution reaction (HER). With electronic and surface structures well‐tailored, the PtFeCo nanostructures exhibit dramatically enhanced performance in HER against commercial Pt/C and other Pt‐based nanoparticles.